Paraquat Toxicogenetics: Strain-Related Reduction of Tyrosine Hydroxylase Staining in Substantia Nigra in Mice - Torres-Rojas, Carolina; Zhao, Wenyuan; Zhuang, Daming; O’Callaghan, James P.; Lu, Lu; Mulligan, Megan K.; Williams, Robert W.; Jones, Byron C. (Frontiers in Toxicology, 2021)
Paraquat (PQ) is a putative risk factor for the development of sporadic Parkinson’s disease. To model possible genetic basis for individual differences in susceptibility to exposure to PQ, we recently examined the effects of paraquat on tyrosine hydroxylase (TH+) containing neurons in the substantia nigra pars compacta (SNc) of six members of the BXD family of mice (n = 2-6 per strain). We injected males with 5 mg kg-1 paraquat weekly three times. The density of TH+ neurons counted by immunocytochemistry at 200X in 8 or more sections through the SNc is reduced in 5 of the 6 strains relative to control (n = 2-5 per strain). TH+ loss ranged from 0 to 20% with SEM of 1%. The heritability was estimated using standard ANOVA and jackknife resampling and is 0.37 ±0.05 in untreated, and 0.47±0.04 in treated animals. These results demonstrate strong genetic modulation and strong GXE variation in susceptibility to PQ exposure and the loss of TH staining in substantia nigra.